Aplikasi Pengelolaan Keuangan Tukang Gigi (K-TUGI) Berbasis Android - Zulkarnain, Iskandar; Fauziyah, Fauziyah; Lestari, Dwi (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Efficient financial management is very important for dentists in carrying out their practice. However, many dentists face difficulties in recording and managing financial transactions systematically. This research aims to design and develop an Android application called K-TUGI to assist dentists in managing income, expenses, and financial reports. The method used in this study is a prototyping approach, which allows the development of the system gradually by involving users from the beginning. The research team conducted observations, interviews, and literature studies to identify user needs and then designed the app's key features. The K-TUGI application provides four main functions: customer data management, income recording, expense recording, and transaction report generation. The implementation results showed that the K-TUGI application was successfully tested using the System Usability Scale (SUS), resulting in a score of 79, which means that the application was rated well by users. The score shows that this application makes it easier for users to manage their finances and provides satisfaction in using it. Thus, K-TUGI can be an effective technology solution for dentists to improve the efficiency of financial management.